2011
DOI: 10.4012/dmj.2011-075
|View full text |Cite
|
Sign up to set email alerts
|

Cellular compatibility of a gamma-irradiated modified siloxane-poly(lactic acid)-calcium carbonate hybrid membrane for guided bone regeneration

Abstract: A bi-layered silicon-releasable membrane consisting of a siloxane-poly(lactic acid) (PLA)-vaterite hybrid material (Si-PVH) microfiber mesh and a PLA microfiber mesh has been developed by an electrospinning method for guided bone regeneration (GBR) application. The bi-layered membrane was modified to a three-laminar structure by sandwiching an additional PLA microfiber mesh between the Si-PVH and PLA microfiber meshes (Si-PVH/PLA membrane). In this study, the influence of gamma irradiation, used for sterilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…They observed no test material-related effects in mortality, inflammation, hematology, serum biochemistry parameters and organ weight in the operated animals at 8, 12, and 24 weeks after implantation [33]. Other scientists have analyzed the biocompatibility of PLA to cells and consistently report good adhesion and no acute cytotoxic effects on fibroblasts [49], MSCs [50], osteoblasts [51] or endothelial cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…They observed no test material-related effects in mortality, inflammation, hematology, serum biochemistry parameters and organ weight in the operated animals at 8, 12, and 24 weeks after implantation [33]. Other scientists have analyzed the biocompatibility of PLA to cells and consistently report good adhesion and no acute cytotoxic effects on fibroblasts [49], MSCs [50], osteoblasts [51] or endothelial cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…For biological applications, there is an additional need for versatile deposition methods in the case of devices with potential clinical applications, which should also stand, without alterations, the sterilization processes [13, 16, 18]. We have successfully demonstrated that PECVD TiO 2 functionalization methodology employed by our group enhances HOB cells response to nonresorbable PET devices and stands for standard u.v.…”
Section: Discussionmentioning
confidence: 99%
“…Well-dispersed nanosized inorganic particles have been described to enhance the mechanical properties of organic materials [10]. A recent study on biosilica influence on the OPG-RANKL ratio in SaOS-2 cells in vitro suggests both osteoinductive and osteogenic potential of biosilica since it combines an upregulation of the genes required for the differentiation with the potential to increase proliferation of the osteogenic cells [18, 24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials selected for drug loading include poly lactic acid (PLA), poly(lactide-co-glycolide) (PLGA), poly(D, L-lactic acid) (PDLLA), polycaprolactone (PCL), and other biocompatible and biodegradable polymers 6,16,19,20) . Among different classes of biodegradable polymers, the thermoplastic aliphatic poly(esters), such as PLA, PLGA and so on, have generated much interest due to their favorable properties 5,[19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%